PPM PENGEMBANGAN WISATA DESA DI DESA SUMBERMULYO KECAMATAN JOGOROTO KABUPATEN JOMBANG - Dwiningwarni, Sayekti Suindyah; Chamariyah, Chamariyah; Endah M, Yurila; Ningsih, Sumita Widiyah; Nur Fauziyah, Ananda Istiqomah; Dwi Andari, Syamsiyah Yuli (Universitas Pelita Harapan, 2023)
Sumber Mulyo is a village located in Jogoroto Jombang District. Sumber Mulyo Village has potential in the field of village tourism because this village is location in an area that has a history of